2009
DOI: 10.1073/pnas.0902319106
|View full text |Cite
|
Sign up to set email alerts
|

Human medial temporal lobe neurons respond preferentially to personally relevant images

Abstract: People with whom one is personally acquainted tend to elicit richer and more vivid memories than people with whom one does not have a personal connection. Recent findings from neurons in the human medial temporal lobe ( epilepsy ͉ hippocampus ͉ memory ͉ familiarity ͉ single-unit recordings H umans are self-absorbed by nature. One virtually infallible method of enhancing memory is simply to relate the to-be-remembered information to one's self. The self-reference effect (1) is a well-documented encoding enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
113
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 100 publications
(124 citation statements)
references
References 48 publications
6
113
0
Order By: Relevance
“…While complementary functions such as novelty/familiarity detection, arousal processing and memory should not be discounted, this study suggests that specific amygdala neurons may scan the environment for relevance amongst novel stimuli (Pedreira et al, 2010). While contemporary neuroscience literature supports amygdala relevance processing (Pessoa & Adolphs, 2010;Sander et al, 2003), intracranial data evidence a direct relation between amygdala neuronal activity and relevance processing, both implicitly (Br azdil et al, 2002;Viskontas, Quiroga, & Fried, 2009) and explicitly (Jenison, Rangel, Oya, Kawasaki, & Howard, 2011). Concretely, these iEEG data have delineated two broad types of amygdala relevance processing: (i) behavioral and (ii) motivational.…”
Section: Relevancementioning
confidence: 67%
See 4 more Smart Citations
“…While complementary functions such as novelty/familiarity detection, arousal processing and memory should not be discounted, this study suggests that specific amygdala neurons may scan the environment for relevance amongst novel stimuli (Pedreira et al, 2010). While contemporary neuroscience literature supports amygdala relevance processing (Pessoa & Adolphs, 2010;Sander et al, 2003), intracranial data evidence a direct relation between amygdala neuronal activity and relevance processing, both implicitly (Br azdil et al, 2002;Viskontas, Quiroga, & Fried, 2009) and explicitly (Jenison, Rangel, Oya, Kawasaki, & Howard, 2011). Concretely, these iEEG data have delineated two broad types of amygdala relevance processing: (i) behavioral and (ii) motivational.…”
Section: Relevancementioning
confidence: 67%
“…Interestingly, family and self were statistically equal to faces of celebrities and strangers. Authors concluded that the amygdala may be involved in processes related to salience/novelty and emotional significance (Viskontas et al, 2009). Together, these single-neuron studies implicate amygdala neurons in relevance processing in both valuation of preferred objects and in viewing faces of potentially self-relevant others (cf.…”
Section: Motivational Relevancementioning
confidence: 97%
See 3 more Smart Citations